Digital Transformation: HDI, Consumption, And Inclusive Economic Growth Link - Zulkarnain Nasution; Henky Japina; Amrizal Amrizal (Economics Development Analysis Journal, 2025)
This research investigates the impact of digital transformation on inclusive economic growth in Indonesia, in light of significant social and economic inequality. While previous studies, particularly in South Africa, have highlighted opportunities for market access, this study focuses on identifying the factors that influence the contribution of digital transformation within the Indonesian context, using Prakash’s theory. A quantitative descriptive approach was employed, utilizing secondary data from the Central Statistics Agency across ten provinces in Sumatra. The analysis applied the Panel Vector Autoregressive (PVAR) method to examine the relationships among variables, including the Human Development Index (HDI), consumption, and social inequality. The findings indicate that, in the long term, both consumption and HDI have a negative impact on inclusive economic growth, with t-statistics of -2.452 and -5.093, respectively. Inequality, however, did not show a significant influence, with a t-statistic of 1.148. Similar trends were observed in the short term. The study concludes that a nuanced understanding of the equitable implementation of digital technology is essential for achieving inclusive economic growth. Notably, the negative influence of HDI on economic inclusion suggests that improvements in quality of life do not always correlate directly with economic growth, offering new insights into the discourse on digital transformation and economic inclusion in Indonesia.